Technology Literacy Applications in Learning Environments 2005
DOI: 10.4018/978-1-59140-479-8.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Technology Literacy and Information Literacy

Abstract: Information technology literacy can be seen as an integration of what are commonly two separate literacies—technology literacy and information literacy. This chapter defines them, reviews issues related to both, and argues that both must be acquired and functionally utilized for students and workers to achieve success in our heavily technology-oriented society and workplace. The authors address learning outcomes and design components that should be considered in training and instructional settings, and give ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As it is usually observed, no matter how old people are, using digital technologies in the digital era have become a vital need (Goodfellow, 2011). Individuals using digital tools in the information age have turned into participative and active individuals who gather, process, and produce information (Sharkey & Brandt, 2008). A digital literate person uses technology effectively in order to do research, reach information sources, read-write and comment efficiently, make reasonable choices, and make right decisions.…”
Section: Digital Life Digital Literacy and Learning Habitsmentioning
confidence: 99%
“…As it is usually observed, no matter how old people are, using digital technologies in the digital era have become a vital need (Goodfellow, 2011). Individuals using digital tools in the information age have turned into participative and active individuals who gather, process, and produce information (Sharkey & Brandt, 2008). A digital literate person uses technology effectively in order to do research, reach information sources, read-write and comment efficiently, make reasonable choices, and make right decisions.…”
Section: Digital Life Digital Literacy and Learning Habitsmentioning
confidence: 99%
“…The characteristics of teachers' beliefs were taken from Grave (2000) that related to teachers' view of language, the social context of language, learning and learners, and teaching [7]. The beliefs of digital literacy were taken from some views [17]; [3], [12] [13]; and [5].…”
Section: Methodsmentioning
confidence: 99%
“…This challenge should be considered by teachers related to the use of digital literacy in improving their teaching. So, it is suggested that in particular, information and communication technology skills should also be involved in teaching programs [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Framework was informed by both the emergent reframing of IL as an overarching metaliteracy emphasising critical agency (Mackey & Jacobson 2011) and the pedagogical frameworks of threshold concepts (Meyer & Land 2003) and backward design (Wiggins & McTighe 2005). (Piele et al, 1986;Wood, 1988) Information literacy (McCrank, 1992;Isbell & Hammond, 1993) Computer & information literacy (Shapiro & Hughes, 1996;Sreenivasulu, 1998) Data (information) literacy (Carlson et al, 2011;Stephenson & Caravello, 2007) Career information literacy (Hollister, 2005;Lin-Stephens et al, 2019) Science literacy (Holden, 2010;Kearns & Hybl, 2005) Network literacy (Devlin, 1997;Hu, 1996) Media literacy (Dilevko & Grewal, 1998;Robinson & Nelson, 2002) Critical literacies (Stonebraker et al, 2017;Swanson, 2004 Archival/primary source literacy (Archer et al, 2009;Morris et al, 2014) Academic literacies (Bent, 2013;Peacock, 2008) Health literacy (Keane, 2009;Lantzy, 2016) Technology literacy (Sharkey & Brandt, 2005;Warnken, 2004) Spatial literacy (Krygier & Peoples, 2005;Nicholson, 2007) Metaliteracy (Mackey & Jacobson, 2011;…”
Section: Academic Success and Student Wellbeingmentioning
confidence: 99%